Relationship between the antioxidant capacity of soy sauces and its impact on lipid oxidation of beef patties. (December 2019) - Ham, Youn-Kyung; Hwang, Ko-Eun; Song, Dong-Heon; Choi, Ji-Hun; Choi, Yun-Sang; Kim, Hyun-Wook
Abstract: The aim of this study was to determine the relationship between in vitro antioxidant capacity of soy sauces and its impact on lipid oxidation in raw and cooked beef patties during 10 days of refrigerated storage. Three commercial soy sauces were used: industrially fermented soy sauce (IS), traditionally fermented Korean soy sauce (KS), and mixed soy sauce (MS). In vitro antioxidant capacity, KS showed the highest total phenol content, whereas IS and MS had a higher Fe 2+ chelating activity than KS ( P  < .05). Heat treatment decreased total phenol content but increased Fe 2+ chelating activity of soy sauces ( P  < .001). In both raw and cooked beef patties, the addition of IS or MS caused a lower 2-thiobarbituric acid reactive substances (TBARS) level than KS throughout the overall storage period ( P  < .05). This preliminary study suggests that the Fe 2+ chelating activity of soy sauce may be one of the major mechanisms in preventing lipid oxidation in meat products.